Do Helpful Mothers Help? Effects of Maternal Scaffolding and Infant Engagement on Cognitive Performance - Clackson, Kaili; Wass, Sam; Georgieva, Stanimira; Brightman, Laura; Nutbrown, Rebecca; Almond, Harriet; Bieluczyk, Julia; Carro, Giulia; Rigby Dames, Brier; Leong, Victoria (Frontiers in Psychology, 2019)
Infants are highly social and much early learning takes place in a social context during interactions with caregivers. Previous research shows that social scaffolding – responsive parenting and joint attention - can confer benefits for infants’ long-term development and learning. However, little previous research has examined whether dynamic (moment-to-moment) adaptations in adults’ social scaffolding are able to produce immediate effects on infants' performance. Here we ask whether infants' success on an object search task is more strongly influenced by maternal behaviour, including dynamic changes in response behaviour,, or by fluctuations in infants' own engagement levels. Thirty-five mother-infant dyads (infants aged 10.8 months, on average) participated in an object search task that was delivered in a naturalistic manner by the child’s mother. Measures of maternal responsiveness (teaching duration; sensitivity) and infant engagement (engagement score; visual attention) were assessed. Mothers varied their task delivery trial by trial, but neither measure of maternal responsiveness significantly predicted infants’ success in performing the search task. Rather, infants’ own level of engagement was the sole significant predictor of accuracy. These results indicate that while parental scaffolding is offered spontaneously (and is undoubtedly crucial for development), in this context children’s endogenous engagement proved to be a more powerful determinant of task success. Future work should explore this interplay between parental and child-internal factors in other learning and social contexts.